2016
DOI: 10.3390/polym8060215
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Epoxy Foam: Optimization of Process Parameters

Abstract: For many years, reduction of fuel consumption has been a major aim in terms of both costs and environmental concerns. One option is to reduce the weight of fuel consumers. For this purpose, the use of a lightweight material based on rigid foams is a relevant choice. This paper deals with a new high temperature epoxy expanded material as substitution of phenolic resin, classified as potentially mutagenic by European directive Reach. The optimization of thermoset foam depends on two major parameters, the reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Their results indicated that the PLA/PBSA foams reveal increased crystallinity and storage modulus as compared to their physically foamed counterparts. Gazzani et al [99] prepared a high-temperature epoxy foam. Table 1 shows the density of epoxy foam samples as a function of temperature.…”
Section: Research Progress Of Various Foaming Methodsmentioning
confidence: 99%
“…Their results indicated that the PLA/PBSA foams reveal increased crystallinity and storage modulus as compared to their physically foamed counterparts. Gazzani et al [99] prepared a high-temperature epoxy foam. Table 1 shows the density of epoxy foam samples as a function of temperature.…”
Section: Research Progress Of Various Foaming Methodsmentioning
confidence: 99%
“…The addition of short fibers to a foaming epoxy system was also found to lead to more homogeneous cell morphology, next to an increase of mechanical performance [10]. Alternatively, syntactic foams, where several types of hollow particles or foam particles with a defined size are mixed into the resin hardener system, are used for weight reduction and cushioning purposes [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…3 The active amine groups of a commercially available curing agent for epoxy resin are blocked by CO 2 to obtain ammonium carbamate, which can be decomposed again by heating above 100 C. However, typical problems of reactive systems have to be solved, above all it is necessary to find the ideal combination between gelation and foaming. 1 In order to solve this kind of problems, syntactic foams have been developed. Bubbles are not produced by foaming but by mixing the liquid resin with hollow microspheres made of glass 4 or polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the case of solid state foaming, 10 all the other contributes refer to epoxy systems. [1][2][3][4][5][6][7][8][9] UP resins are very difficult to foam because of the low roomtemperature viscosity (lower than epoxies) and the fast polymerization kinetics. Recently, Zhang et al have evaluated urea-activated 4,4 0 -oxibis-(benzenesulfonyl hydrazide) OBSH as foaming agent to produce UP foams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation